Interventional Glaucoma: Improving the Patient-Provider Educational Exchange - Katz LJ; Myers JS; Herndon Jnr LW; Kresch YS; Hengerer FH (Clinical Ophthalmology)
L Jay Katz,1,2 Jonathan S Myers,1 Leon W Herndon Jnr,3 Yocheved Shira Kresch,4 Fritz H Hengerer5,6 1Wills Eye Hospital, Philadelphia, PA, USA; 2Glaukos Corporation, Aliso Viejo, CA, USA; 3Duke University Eye Center, Durham, NC, USA; 4Department of Ophthalmology, Wayne State University School of Medicine, Detroit, MI, USA; 5Department of Ophthalmology, Buergerhospital, Frankfurt, Germany; 6University Eye Hospital, University of Heidelberg, Heidelberg, GermanyCorrespondence: L Jay Katz, Glaukos Corporation, One Glaukos Way, Aliso Viejo, CA, 92656, USA, Tel +01 949-367 9600, Fax +01 949 367 9984, Email jkatz@glaukos.comAbstract: Glaucoma treatment is beginning to undergo an evolution, moving away from topical medication-based therapies toward more proactive minimally invasive interventions. This shift towards an “interventional glaucoma” treatment paradigm has been shown to benefit patients, providers, and society. A key component of effectively implementing this approach is education about the importance of glaucoma diagnosis and treatment, as well as the various treatment modalities available. Such education is relevant not only for patient but also patients’ support networks, ophthalmologists, optometrists, third-party payers, and policy-makers. Education can occur both within and outside the clinical setting. The present article provides an overview of the diverse educational methods available for glaucoma patients, including those based on patient-provider interactions and those based on internet and printed material. Examples of the former could include general and specific verbal instruction, motivational interviewing, or community-based educational workshops, while examples of the latter could include office-based movies or printed materials, virtual reality headset educational videos, artificial intelligence-assisted education, or self-directed internet videos and articles. By empowering patients with knowledge and an up-to-date awareness of treatment options, effective education can be a valuable part of making an interventional glaucoma treatment paradigm possible.Keywords: MIGS, education, intervention/interventional, glaucoma, surgery